Manjud, Mustafa Mahmoud. “Values and the Epistemological System in Political Thought: A Comparative Study of the Contributions of al-Ghazālī and Machiavelli,” Year 5, Issue 19 (Winter 1420 AH/ 1999 CE), Pp. 31-83. - منجود, مصطفى محمود (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 1999)
Mustafa Manjud addresses the concepts of “values” and “the epistemological system,” and discusses the value elements of the epistemological system in the thought of al-Ghazālī and Machiavelli, the highest value in their value systems, and the role of value for certain institutions of the epistemological system. He concludes by stressing that the intellectual uṣūl (fundamentals) and the civilizational reality for either one of them limited their contribution in the concept of values, epistemological system, and political thought, and that although their thought may not intersect at all, a coexistence between both thoughts is possible if we utilize the initiatives of agreement and reduced the negative consequences of disagreement. Manjud’s study calls on those concerned with the Islamic epistemological system to rediscover it, its structure, components, purposes, and tools so as to revive its civilizational message.